2012
DOI: 10.2460/ajvr.73.5.620
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a single intramuscular injection of ceftiofur crystalline-free acid in American black ducks (Anas rubripes)

Abstract: On the basis of the time that CFAE concentrations were higher than the target plasma concentration, a dosing interval of 3 days can be recommended for future multidose CCFA studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…These studies have revealed a higher C max (lg/ml) in the helmeted guineafowl (5.26), ball python (7.096 61.95), and American black duck (13.1) compared with that measured in the California sea lion. 1,15,22 Common bacterial organisms isolated from pinnipeds include Leptospira spp., Escherichia coli, Staphylococcus spp., Streptococcus spp., and Salmonella, among others. 8,10,16,17,21 Ceftiofur has been shown to be an effective antibiotic against these organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed a higher C max (lg/ml) in the helmeted guineafowl (5.26), ball python (7.096 61.95), and American black duck (13.1) compared with that measured in the California sea lion. 1,15,22 Common bacterial organisms isolated from pinnipeds include Leptospira spp., Escherichia coli, Staphylococcus spp., Streptococcus spp., and Salmonella, among others. 8,10,16,17,21 Ceftiofur has been shown to be an effective antibiotic against these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Use of EXCEDE in nondomestic species is increasing, and pharmacokinetic analysis and safety have been reported in Asian elephants (Elephas maximus), ball pythons (Python regius), helmeted guinea fowl (Numida meleagris), and American black ducks (Anas rubripes). 1,2,15,22 Currently, EXCEDE is used for treatment of bacterial infections in various pinniped and cetacean species and was recently administered to free-ranging live humpback whales (Megaptera novaeangliae). 14 Although the use of EXCEDE in marine mammals is increasing, pharmacokinetics for the drug have not been reported for any species, and dosing and frequency have been extrapolated from domestic species.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other cephalosporin, the time to reach a maximum serum concentration (Tmax) was disagreed with those reported in Ceftiofur in chickens 2.51± 0.088 h, (Dalia, et al, 2015),Cefquinome in broiler chickens 2. 8±0.19h, (El-Mahdy, et al, 2015), Ceftiofur in rabbits 0.25 h (Kamil, et al, 2015), Cefquinome in black swans 0.39 h (Zhao et al, 2017), Ceftiofur crystallinefree acid in American black ducks 24 h, (Hope et al, 2012), Ceftiofur sodium in adult cockatiels and Amazon parrots 0.5 h, (Tell, et al, 1998),Ceftiofur crystalline free acid in American flamingos 7.49 ±1.9 h (Kilburn, et al, 2015), Ceftiofur crystalline-free acid in healthy adult helmeted guinea fowl 19.3 ±9.71 h (Kimberlee, et al, 2011), Cefquinome in chickens 0.25 ± 0.06 h (Xie, et al, 2013) and Cefquinome in ducks 0.38 ± 0.06 h (Yuan et al, 2011). The mean peak serum concentration of cefepime (Cmax) was (193.06±2.27 μg/ml) after i.m administration of 100 mg/kg.bw.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that ceftiofur sodium exerts bactericidal effect on tested microorganisms at concentration equal to or at most one doubling dilution above MIC. Many authors were reportedthat high activity of ceftiofur against P. multocida isolated from cattle, swine and duck in vitro [10,12,28,29]. Also, some authors [8] reported that the MIC of ceftiofur sodium required to inhibit growth of 90% of isolates of E. coli, Pasteurella spp., Klebsiella spp., and beta-haemolytic Streptococci was <0.5 microg/ml, and intravenous administration of ceftiofur sodium at rate of 5 mg/kg every 12 h would provide sufficient coverage for the treatment of susceptible bacterial isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It is used for treatment of respiratory tract diseases in cattle, sheep, horse and swine that are caused by P. multocida and P. haemolytica [6][7][8][9][10]. It was reported for the control of P. multocida infection in balady chickens [2], and also for the control of terminal bacterial infection in one day old broiler chickens [11], and American black ducks [12]. The effect of therapeuticceftiofur administration to dairy cattle on E. coli was studied [13].…”
Section: Introductionmentioning
confidence: 99%